2023
DOI: 10.1186/s12886-023-03222-7
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between refractive errors and ocular biometric parameters in children and adolescents: a systematic review and meta-analysis

Zengrui Zhang,
Jingyu Mu,
Jing Wei
et al.

Abstract: Background Refractive errors are one of the most common ocular conditions among children and adolescents, with myopia showing an increasing prevalence and early onset in this population. Recent studies have identified a correlation between refractive errors and ocular biometric parameters. Methods A systematic search was conducted in electronic databases including PubMed, EMBASE, Cochrane Library, Web of Science, and Medline from January 1, 2012, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 150 publications
0
0
0
Order By: Relevance
“…In addition, in the current lens and tilt also to be lower in HM eyes than the LMMs, which is also in line with previous investigations. 37,40 Notably, we found that the lens of HM eyes seemed to change more than the LMM eyes during 2D viewing. This may explain why HM eyes may be more prone to visual fatigue caused by intense accommodation.…”
Section: Parametersmentioning
confidence: 69%
“…In addition, in the current lens and tilt also to be lower in HM eyes than the LMMs, which is also in line with previous investigations. 37,40 Notably, we found that the lens of HM eyes seemed to change more than the LMM eyes during 2D viewing. This may explain why HM eyes may be more prone to visual fatigue caused by intense accommodation.…”
Section: Parametersmentioning
confidence: 69%
“…With the development of children's bodies, they exhibit varying degrees of changes in ocular biometric parameters [11]. One study showed that ocular biometric parameters are potential biomarkers for assessing myopia in children and adolescents [12]. Axial length is a major determinant of myopia [13].…”
Section: Introductionmentioning
confidence: 99%